Indole acrylonitriles as potential anti-hyperglycemic agents: Synthesis, α-glucosidase inhibitory activity and molecular docking studies. Issue 21 (1st November 2020) - Solangi, Mehwish; Kanwal,; Mohammed Khan, Khalid; Saleem, Faiza; Hameed, Shehryar; Iqbal, Jamshed; Shafique, Zainab; Qureshi, Urooj; Ul-Haq, Zaheer; Taha, Muhammad; Perveen, Shahnaz
Graphical abstract: Highlights: Indole acrylonitriles (3 –23 ) were synthesized and characterized through different spectroscopic techniques. The synthetic molecules were evaluated for their potential for α- glucosidase inhibition. Acarbose (IC50 = 2.91 ± 0.02 μM) was used as standard. Molecular docking of synthetic compounds was performed to verify the binding interactions of ligand with the active site of enzyme. Abstract: One of the most prevailing metabolic disorder diabetes mellitus has become the global health issue that has to be addressed and cured. Different marketed drugs have been made available for the treatment of diabetes but there is still a need of introducing new therapeutic agents that are economical and have lesser or no side effects. The current study deals with the synthesis of indole acrylonitriles (3 –23 ) and the evaluation of these compounds for their potential for α- glucosidase inhibition. The structures of these synthetic molecules were deduced by using different spectroscopic techniques. Acarbose (IC50 = 2.91 ± 0.02 μM) was used as standard in this study and the synthetic molecules (3 –23 ) have shown promising α- glucosidase inhibitory activity. Compounds 4, 8, 10, 11, 14, 18, and 21 displayed superior inhibition of α -glucosidase enzyme in the range of (IC50 = 0.53 ± 0.01–1.36 ± 0.04 μM) as compared to the standard acarbose. Compound 10 (IC50 = 0.53 ± 0.01 μM) was the most effective inhibitor of this library and displayed many folds enhanced activity in contrast to the standard. Molecular docking of synthetic compounds was performed to verify the binding interactions of ligand with the active site of enzyme. This study had identified a number of potential α- glucosidase inhibitors that can be used for further research to identify a potent therapeutic agent against diabetes.